IMPROVING THERMAL AND ELECTRICITY GENERATION PERFORMANCE OF PHOTOVOLTAIC/THERMAL (PV/T) SYSTEMS USING HYBRID NANOFLUID - Swese, Ettahır El Hadı O.; Sözen, Adnan; Rezaeızadeh, Rezvan; Hançerlioğulları, Aybaba; Aytaç, İpek; Variyenli, Halil İbrahim; Çakır, Mutlu Tarık (Begell House, 2024)
Solar energy is a safe and clean source of energy, available on the Earth throughout the year. A photovoltaic/thermal (PV/T) system is a device designed to take solar energy and convert it into electrical/thermal energy. Photovoltaic/ thermal systems can also be useful to produce hot fluid (usually water) along with the generation of electrical energy. In addition, the electric generating performance of PVs increases with heat discharging ability of thermal system, which also prevents overheating in PV systems. Nanofluid is a new generation heat transfer fluid that delivers higher thermal conductivity and heat transfer rate compared to conventional fluids. The thermal conductivity of the nanofluid depends on the size of the nanoparticles, concentration of the nanofluid, and the method of its preparation. In this study, it is aimed to increase the thermal heat transfer of the PV/T system by using hybrid nanofluids, manufactured by adding 0.5% Fe2O3 and Fe3O4 nanoparticles to the water as a working fluid. By using hybrid nanofluids, increase in bidirectional performance along with enhanced cooling is achieved. In the experimental study, more heat was withdrawn from the heated PV panels by utilizing the high thermal conductivity of the hybrid nanofluid, and the best improvement in total efficiency was obtained as 86% for the hybrid nanofluid. With the use of hybrid nanofluids in the cooling circuit, the electrical and thermal efficiency of the PV panel has reached to overall 81% on average basis.
Keywords: 13. Climate action; 7. Clean energy